Solving Fuzzy Rayleigh Model with Application - Suhaila N. Abdullah (مجلة بغداد للعلوم, 2023)
In this article, deriving and estimating the two parameters of Rayleigh distribution by utilizing the maximum likelihood estimation method, regular least squares estimation method and moment estimation method. The simulation technique for many samples sites and many numbers of initial values are used, then attaining that the moment estimation method are the best one from another method by using mean squares error procedures. The interval estimation is used to find the estimator of location and scale parameters for Rayleigh distribution. The triangular membership functions are employed to find the fuzzy estimate parameters for the moment method of Rayleigh distribution. Finally utilizing the ranking function to transform the fuzzy parameters to crisp parameters and include that the fuzzy estimate parameters are the best.